Nitric oxide restores peripheral blood mononuclear cell adhesion against hypoxia via NO‐cGMP signalling. (27th January 2020) - Behera, Jyotirmaya; Nagarajan, Shunmugam; Saran, Uttara; Kumar, Ravi; Keshri, Gaurav K.; Suryakumar, Geetha; Chatterjee, Suvro
Abstract : Hypoxia is the most detrimental threat to humans residing at high altitudes, affecting multifaceted cellular responses that are crucial for normal homeostasis. Inhalation of nitric oxide has been successfully implemented to combat the hypoxia effect in the high altitude patients. We hypothesize that nitric oxide (NO) restores the peripheral blood mononuclear cell‐matrix deadhesion during hypoxia. In the present study, we investigate the cellular action of exogenous NO in the hypoxia‐mediated diminution of cell‐matrix adhesion of PBMNC and NO bioavailability in vitro. The result showed that NO level and cell‐matrix adhesion of PBMNC were significantly reduced in hypoxia as compared with normoxia, as assessed by the DAF‐FM and cell adhesion assay, respectively. In contrast, cellular oxidative damage response was indeed upregulated in hypoxic PBMNC. Further, gene expression analysis revealed that mRNA transcripts of cell adhesion molecules (Integrin α5 and β1) and eNOS expressions were significantly downregulated. The mechanistic study revealed that administration of NO and 8‐Br‐cGMP and overexpression of eNOS‐GFP restored the basal NO level and recovers cell‐matrix adhesion in PBMNC via cGMP‐dependent protein kinase I (PKG I) signalling. In conclusion, NO‐cGMP/PKG signalling may constitute a novel target to recover high altitude–afflicted cellular deadhesion. Significance of this study: Cellular adhesion is a complex multistep process. The ability of cells to adhere to extracellular matrix is an essential physiological process for normal homeostasis and function. Hypoxia exposure in the PBMNC culture has been proposed to induce oxidative damage and cellular deadhesion and is generally believed to be the key factor in the reduction of NO bioavailability. In the present study, we demonstrated that NO donor or overexpression of eNOS‐GFP has a protective effect against hypoxia‐induced cellular deadhesion and greatly improves the redox balance by inhibiting the oxidative stress. Furthermore, this protective effect of NO is mediated by the NO‐cGMP/PKG signal pathway, which may provide a potential strategy against hypoxia.